2014
DOI: 10.1007/s00018-014-1575-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and the endocannabinoid system: an overview

Abstract: Recognized as a "disease modifier", physical activity (PA) is increasingly viewed as a more holistic, cost-saving method for prevention, treatment and management of human disease conditions. The traditional view that PA engages the monoaminergic and endorphinergic systems has been challenged by the discovery of the endocannabinoid system (ECS), composed of endogenous lipids, their target receptors, and metabolic enzymes. Indeed, direct and indirect evidence suggests that the ECS might mediate some of the PA-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 191 publications
1
78
0
Order By: Relevance
“…16 The protective effects of PA on neurogenesis have been demonstrated through increases in neurotrophic factors, including BDNF and insulin-like growth factor-1 (IGF-1) levels. [16][17][18] Alternative hypotheses have also been proposed for the anxiolytic effects of PA on activating the endocannabinoid system 19,20 and modulating adenosine receptors. 21 PA increases circulating levels of endocannabinoids, including anandamide.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 The protective effects of PA on neurogenesis have been demonstrated through increases in neurotrophic factors, including BDNF and insulin-like growth factor-1 (IGF-1) levels. [16][17][18] Alternative hypotheses have also been proposed for the anxiolytic effects of PA on activating the endocannabinoid system 19,20 and modulating adenosine receptors. 21 PA increases circulating levels of endocannabinoids, including anandamide.…”
mentioning
confidence: 99%
“…21 PA increases circulating levels of endocannabinoids, including anandamide. 19,20 In turn, these neuromodulators induce antianxiety and antidepressive effects by regulating the signaling of other neurotransmitters (i.e., dopaminergic and glutamatergic signaling) and reducing metabolism in the pre-frontal cortex. 19,20 Cannabinoids may also have anxiolytic effects by regulating the HPA axis and enhancing BDNF expression.…”
mentioning
confidence: 99%
“…Anandamide is an endogenous cannabinoid neurotransmitter that binds to cannabinoid receptors (Tantimonaco et al, 2014). Aerobic exercise causes an increase in the plasma anandamide level and it has been observed that moderate intensity exercise causes the greatest increase in plasma anandamide concentration.…”
Section: Neurobiological Effectsmentioning
confidence: 99%
“…Aerobic exercise causes an increase in the plasma anandamide level and it has been observed that moderate intensity exercise causes the greatest increase in plasma anandamide concentration. Increased plasma anandamide concentration is associated with psychoactive effects because it can cross the blood-brain barrier to act on the central nervous system (Tantimonaco et al, 2014).…”
Section: Neurobiological Effectsmentioning
confidence: 99%
“…Multiple functions are suggested for AEA, including modulation of pain, memory, inflammation, and energy metabolism. AEA may modulate the reward system via dopamine release [65] and be induced during physical activity [66]. Oleoylethanolamide (OEA) (C18:1) is a PPAR-α agonist [67] but is also a TRPV 1 activator [68] and a GPR 119 activator [69].…”
Section: N-acylethanolamines (Naes)mentioning
confidence: 99%